The State of food and agriculture 2000. (Rome Food and Agriculture Organization of the United Nations, 2000)
The past half century has seen spectacular progress in agricultural technology and productivity, but far from sufficient progress in poverty alleviation and food security, particularly in rural areas. This issue investigates some both the positive and negative changes that occurred in the second half of the twentieth century. It addresses the social and economic impact of agricultural modernization, the role of staple food production in nutrition and food security, trends in productivity and the politics involved in preventing some population groups from the development process.
"TC/P/X4400E/6.00/4000"--P. [4] of back cover.
"The statistical material in this publication has been prepared from information available to FAO up to March 2000"--T.p. verso.
Title on diskette: Time series for SOFA 2000. "Time series data for 150 countries, country groups and regions are provided in English, French and Spanish on an accompanying diskette, including FAOSTAT TS software to ensure easy access and use"--P. [4] of cover.
Includes bibliographical references.
System requirements for acoompanying disk: IBM or compatible PC; KB RAM; DOS 3.0 or higher; 300 KB of available RAM and graphics capability; VGA, EGA, MCGA, CGA or Hercules monochrome.
Keywords: Agricultural assistance; Agriculture; Food relief; Food supply; Poverty; ABASTECIMIENTO DE ALIMENTOS; AGRICULTURA; ECONOMIA AGRARIA